Analisis Kebutuhan Pengembangan Media Pembelajaran di SD pada Kurikulum Merdeka - Purwanti, Peni; Muksar, Makbul; Rufiana, Intan Sari (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to find out the need for learning media in the independent curriculum in elementary schools in Talun District, Blitar Regency, based on the numeracy ranking on the education report card. This research is a qualitative descriptive study. The data collection technique used was observation, interviews and documentation. The population in this study were all elementary schools in Talun District, Blitar Regency. The sampling technique in this research uses a purposive sampling technique where the sample is divided into three numerical ranks in the education report, namely upper, middle and lower. Based on the research results, it shows that several elementary schools in SD in Talun District, Blitar Regency have maximized the use of media in carrying out the learning process. For certain subjects, such as local content, some teachers in several schools have difficulty developing learning media so they rarely use media to convey material to students.